2016
DOI: 10.1111/joa.12514
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Achilles tendon at the insertion on the calcaneal tuberosity

Abstract: Findings on the twisting structure and insertional location of the AT on the calcaneal tuberosity are inconsistent. Therefore, to obtain a better understanding of the mechanisms underlying insertional Achilles tendinopathy, clarification of the anatomy of the twisting structure and location of the AT insertion onto the calcaneal tuberosity is important. The purpose of this study was to reveal the twisted structure of the AT and the location of its insertion onto the calcaneal tuberosity using Japanese cadavers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 21 publications
6
50
2
1
Order By: Relevance
“…We used two methods, an established one, described by van Gils et al (), and a new one based on quantitively measuring the different torsion angles using an open‐source computer software. Although the new data does not integrate well with the data of van Gils et al (), a certain degree of accordance with newer data of Edama et al (, ) could be found. Furthermore, the correlation of the torsions could only be identified after including all parts of the triceps surae muscle.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…We used two methods, an established one, described by van Gils et al (), and a new one based on quantitively measuring the different torsion angles using an open‐source computer software. Although the new data does not integrate well with the data of van Gils et al (), a certain degree of accordance with newer data of Edama et al (, ) could be found. Furthermore, the correlation of the torsions could only be identified after including all parts of the triceps surae muscle.…”
Section: Discussioncontrasting
confidence: 66%
“…Looking at the LG, for example, a strong positive, i.e., outward or lateral, respectively, the rotation was seen in some specimens. This might correspond to the “moderate” (Type II) and “extreme” (Type III) rotation types seen in the study by Edama et al (, ). Accordingly, when the LG rotated outwardly, the MG also showed a slight outward rotation.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations